The Relationship Between Smoking Habits And The Incidence Of Hypertension At Puskesmas Kapasa, Makassar City - Demira Kogoya; Andi Sulfikar; Rusli Taher; Indah Restika BN (Indonesian Journal of Nursing and Health Care, 2024)
Background: Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. One preliminary study conducted at the Kapasa Health Center in Makassar City found that the average person with hypertension has a smoking habit. Research reveals that the prevalence of smokers in the hypertensive group is higher than that of the pre-hypertensive group. Purpose: The purpose of this study is to try to see the relationship between smoking habits and the incidence of hypertension in patients at the Kapasa Health Center in Makassar City.Methods: This study is an analytical descriptive study with a cross-sectional research design to determine the relationship between smoking habits and increased blood pressure in the Kapasa Health Center in Makassar City.Result:  Based on univariate analysis, the results showed that out of 20 respondents of hypertensive patients, there were 17 people who did not have smoking habits (85.0%), while hypertensive patients who had smoking habits were only 3 people (15.0%), so that in this study the most respondents showed non-smoking habits with 17 respondents (85.0%) of 20 respondents.Conclusion:  Based on the results of research and discussion of the relationship of smoking habits to the incidence of hypertension in patients of the kapasa health center in the city of Makassar, it can be concluded that there is no significant relationship between smoking habits and the incidence of hypertension indicated by a p value of .016.